The effects of nectar-robbing on fruit production in Sparattosperma leucanthum (Bignoniaceae) - Polatto, Leandro Pereira [UNESP]; Chaud-Netto, José [UNESP]; AlvesJúnior, Valter Vieira; Dutra, João Cloves Stanzani (My University, 2011)
Many animals behave as robbers or thieves of floral resources, causing damage to floral tissues or consuming resources used to attract pollinators, or producing effects similar to emasculation by reducing the pollen load in the anthers (which generally results in losses in terms of sexual reproduction). The present work examined the direct and indirect impacts caused by nectarrobbing on the reproductive success of Sparattosperma leucanthum. Different manipulations of the flowers were tested to determine if fruit production was influenced by the perforations made in the floral tissues (direct damage), and if there were changes in visitation frequencies or in the behaviors of effective pollinators (indirect damage). Perforations made by nectar robbers did not lower the reproductive success of the plant species studied. The bee Trigona spinipes was the most frequent visitor and caused the largest perforations in the calyx and corolla of S. leucanthum. Additionally, we noted the occurrence of pollen theft by this same bee in flowers that had been protected against nectar-robbing. These results suggest that if S. leucanthum had developed a mechanism of resistance to robbery by T. spinipes it would probably have experienced even lower pollination levels as a result of reductions in the quantities of pollen available for transfer by effective pollinators. We were not able to evaluate if nectar depletion through robbery modified the behavior of the effective pollinators (bumblebees of the genus Bombus).
Keywords: Bees; Effective pollinator; Floral damage; Resource larceny; Trigona spinipes